2018
DOI: 10.1088/1748-605x/aac7a6
|View full text |Cite
|
Sign up to set email alerts
|

Performance of marrow stromal cell-seeded small-caliber multilayered vascular graft in a senescent sheep model

Abstract: Failure of small-caliber grafts, used as bypass or reconstructive grafts in cardiovascular treatments, is often caused by thrombosis and stenosis. We have developed a multilayered, compliant graft with an electrospun heparin-encapsulated core and collagen-chitosan shell. Herein, the performances of acellular and cell-seeded grafts were evaluated in adult sheep for preclinical assessment. Allogeneic ovine marrow stroma cells (MSCs) were uniformly attached to the lumen of cell-seeded grafts. Interposition grafts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Thereby, heparin–chitosan-coated grafts would be a very interesting option for small-diameter vascular grafts, even if the continuous ingrowth of ECs from the anastomic region could be impaired. It is known that intimal hyperplasia caused by smooth muscle cells at the anastomosis is one of the causes for graft failure [ 109 , 110 ], and interestingly, Chupa et al found impaired proliferation and cell spread of smooth muscle cells on heparin–chitosan-modified surfaces [ 32 ], which is also confirmed by the findings of Clowes et al [ 111 ]. Thus, a heparin–chitosan coating could probably limit the intimal hyperplasia at the anastomosis to the native vessel, while promoting endothelialization with EPCs originating from the donor blood, thereby overcoming the disadvantage of reduced attachment of HSVECs.…”
Section: Discussionmentioning
confidence: 72%
“…Thereby, heparin–chitosan-coated grafts would be a very interesting option for small-diameter vascular grafts, even if the continuous ingrowth of ECs from the anastomic region could be impaired. It is known that intimal hyperplasia caused by smooth muscle cells at the anastomosis is one of the causes for graft failure [ 109 , 110 ], and interestingly, Chupa et al found impaired proliferation and cell spread of smooth muscle cells on heparin–chitosan-modified surfaces [ 32 ], which is also confirmed by the findings of Clowes et al [ 111 ]. Thus, a heparin–chitosan coating could probably limit the intimal hyperplasia at the anastomosis to the native vessel, while promoting endothelialization with EPCs originating from the donor blood, thereby overcoming the disadvantage of reduced attachment of HSVECs.…”
Section: Discussionmentioning
confidence: 72%
“…Each article analyzed in this review created its own TEVG, although there were certain materials that were commonly used, such as biodegradable polymers, or biological materials. Notably, some researchers used heparin in the design of TEVGs ( Jiang et al, 2016 ; Koobatian et al, 2016 ; Hu et al, 2017 ; Ju et al, 2017 ; Madhavan et al, 2018 ; Xu et al, 2018 ; Jin et al, 2019a ; Jin et al, 2019b ; Ran et al, 2019 ; Shi et al, 2019 ; Smith et al, 2019 ; Wang et al, 2019 ). The addition of heparin to materials prevents thrombosis and enhances biocompatibility ( Aslani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al immobilized reactive Co (III) salen species onto sCNCs to produce heterogeneous catalysts for the synthesis of cyclic carbonates from propylene oxide and CO 2 [109]. These catalysts achieved a near quantitative yield in 24 h at low CO 2 pressure of 0.1 MPa with demonstrated reusability in four reaction cycles.…”
Section: Catalysismentioning
confidence: 99%